Deswelling behaviour of ionic microgel particles from low to ultra-high densities. Issue 20 (10th May 2018) - Nöjd, Sofi; Holmqvist, Peter; Boon, Niels; Obiols-Rabasa, Marc; Mohanty, Priti S.; Schweins, Ralf; Schurtenberger, Peter
Abstract : The swelling of ionic microgel particles is measured at a wide range of concentrations using a combination of light, X-ray and neutron scattering techniques. Theoretical modeling as well as simulations are used to interpret the data. Abstract : The swelling of ionic microgel particles is investigated at a wide range of concentrations using a combination of light, X-ray and neutron scattering techniques. We employ a zero-average contrast approach for small-angle neutron scattering experiments, which enables a direct determination of the form factor at high concentrations. The observed particle size initially decreases strongly with the particle concentration in the dilute regime but approaches a constant value at intermediate concentrations. This is followed by a further deswelling at high concentrations above particle overlap. Theory and experiments point at a pivotal contribution of dangling polymer ends to the strong variation in size of ionic microgels, which presents itself mainly through the hydrodynamics properties of the system.